AB0468 Clinical and ultrasonographic effectiveness in two cohorts of rheumatoid arthritis patients treated with abatacept: a real life study. (12th June 2018) - Parisi, S.; Ditto, M.C.; Scarati, M.; Priora, M.; Peroni, C.L.; Fusaro, E.
Abstract : Background: Synovitis in Rheumatoid Arthritis (RA) is a phenomenon related to the development of erosions and progressive structural damage; early synovitis improvements are successfully associated with long-term clinical and structural outcomes. Objectives: The aim of this study was to evaluated the efficacy of abatacept in two cohort of patients treated with Abatacept as the first and second or third line of treatment. Methods: We evaluated patients affected by RA (according to ACR 2010 criteria) and were divided into two groups: Group A : patients with moderate or severe active RA, non-responders to Metothrexate (MTX), bDMARDs naïve, treated with Abatacept 125 mg/wk; Group B : patients with moderate or severe active RA, non-MTX and anti-TNF responders, treated with Abatacept 125 mg/wk; The concomitant treatment with MTX was maintained unchanged in those patients who were taking it at stable doses before the start of the study (10–15 mg/week for ≥28 days); concomitant therapies such as low-dose systemic CS (prednisone ≤7.5 mg/day) and NSAIDs have been maintained for at least 4 weeks if stable. The activity of RA was calculated with the DAS28-CRP according to the clinical practice protocol (week 0, 4, 12, 24). The Ultrasound (US) evaluation of the synovitis was done according to the Omeract criteria (Grey Scale and PDUS score: 0 to 3). Results: We recruited consecutively 34 patients with RA, 16 pts (male n=4; 25, 00%) took Abatacept as the first line (Group A), and 18 pts (males n=5; 27.70%) took Abatacept as followed by another anti-TNF drugs (Group B). The mean age was 57.2±10.7 years (median 60, range 45–72); mean of DAS28 at baseline was 4.8±0.9 (median 4.7; range 3.9–5.6); mean duration of the disease was 15.3±5.7 years (median 10; range 3–22). Tab.1 A constant improvement of the DAS28 score is shown in both groups examined until the end of the follow up, resulting respectively -Δ 2.0 for Group A (p<0.05) and -Δ 2.1 (p<0.05) for Group B. The total PDUS score decreased in both groups from week 4, with a mean change (95% CI) compared to baseline of −0.8 (range −1.4/–0.2) and progressive mean significant improvement until follow-up (Gr.A p<0.05; Gr.B p<0.05). No serious adverse events or infections were observed. Patients with ACPA positive showed a greater improvement trend compared to other patients in both groups (p: 0, 068). Figure 1. Conclusions: The treatment with Abatacept, administered in the first or second or third line, has shown significant efficacy in reducing the synovial inflammation in patients with RA, monitored with clinical and ultrasonographic outcome. Moreover, we have not demonstrate statistically significant differences between two groups into the timing of improvement. Reference: [1] D'Agostino T, et al. Early Response to Abatacept Plus MTX in MTX-IR RA Patients Using Power Doppler Ultrasonography: an open label Study.Ann Rheum Dis2012;71:18. Disclosure of Interest: None declared